1995
DOI: 10.1063/1.114084
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity at the Al/Si3N4 interfaces

Abstract: Reactive ion etching of Al and Al-Si films with CCl4, N2, and BCl3 mixtures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…8-10, and the best values of the parameters in Table 3. As mentioned by the E811 collaboration [18], a logarithmic fit favours their new measurement. However, for our purpose, we must point out that, despite the fact that the fit seems better, the pomeron contribution becomes negative for √ s < 12 GeV.…”
Section: The Question Of Unitarization and Alternative Modelsmentioning
confidence: 92%
“…8-10, and the best values of the parameters in Table 3. As mentioned by the E811 collaboration [18], a logarithmic fit favours their new measurement. However, for our purpose, we must point out that, despite the fact that the fit seems better, the pomeron contribution becomes negative for √ s < 12 GeV.…”
Section: The Question Of Unitarization and Alternative Modelsmentioning
confidence: 92%
“…Even with the sputtering conditions used in this work, there is some incorporation of oxygen, both at the interface with the substrate, which is the first part of the film to be deposited, and the top layer that is exposed to air. It has been shown that the initial layers of Al deposited on SiO 2 or Si 3 N 4 will reduce the oxide or nitride to form A1 2 O 3 or A1N, respectively 33,34 Oxygen that was adsorbed onto the surface of a substrate previously exposed to air will also be incorporated. So the Al closest to the substrate will contain some amount of oxygen and/or nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Tevatron data were of central importance for determining the increase of the secondary particle multiplicity. There was, however, a considerable uncertainty [12] in the extrapolation of the model predictions to higher energy due to the different cross section measurements indicating either a moderate [13,14] or a fast [15] rise of the total cross section.…”
Section: Introductionmentioning
confidence: 99%